1994
DOI: 10.1073/pnas.91.14.6604
|View full text |Cite
|
Sign up to set email alerts
|

The Fenton oxidation mechanism: reactivities of biologically relevant substrates with two oxidizing intermediates differ from those predicted for the hydroxyl radical.

Abstract: The application of kinetic probes that allow Materials. NDMA and 30% hydrogen peroxide were purchased from Sigma. Perdeuterio NDMA (NDMA-d6) was synthesized as described (20). Benzyl alcohol, dimethyl sulfoxide (DMSO), t-butanol, CH30H, C2H3OH, and FeSO4-7H20 were purchased from Aldrich.Rate Stude. The kinetic experiments were performed using a Hi-Tech Scientific model SR-51MX multi-mixing stopped-flow spectrophotometer. Generally, the reactions were initiated by coinjecting into the reaction chamber an aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 19 publications
2
70
0
2
Order By: Relevance
“…7). These ions most likely react with peroxide to form a metal-oxo complex or ⅐ OH through Fenton-type chemistry (57,58 Although there were differences in the relative efficacy of each ion to catalyze nitration, this could be attributed to differences in solubility or additionally to possible variations in preference for different protein ligand environments. In direct contrast to hemin, nitration by Fe 2ϩ during the NO͞O 2 Ϫ reaction resulted in nitration only at limited fluxes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7). These ions most likely react with peroxide to form a metal-oxo complex or ⅐ OH through Fenton-type chemistry (57,58 Although there were differences in the relative efficacy of each ion to catalyze nitration, this could be attributed to differences in solubility or additionally to possible variations in preference for different protein ligand environments. In direct contrast to hemin, nitration by Fe 2ϩ during the NO͞O 2 Ϫ reaction resulted in nitration only at limited fluxes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute increase in the level of ortho-tyrosine was ϳ10-fold higher than that of o,oЈ-dityrosine. It should be noted that copper plus H 2 O 2 is a metal-catalyzed oxidation system that generates other reactive species in addition to HO ⅐ (42,43). In vitro studies have demonstrated, however, that the relative product yields of o,oЈ-dityrosine and ortho-tyrosine are similar in model proteins exposed to copper plus H 2 O 2 or ionizing radiation (a relatively pure source of HO ⅐ ; Ref.…”
Section: -Nitrotyrosine Ooј-dityrosine and Ortho-tyrosine In Braimentioning
confidence: 99%
“…The main experimental evidence is based on the capacity of Fenton reaction to oxidate substrates in the presence of •OH quenchers (24)(25)(26) . Ferryl intermediary in Fenton reaction was proposed by Brain y Gorin (27) , according to (8 (28) , UV/Vis stopped-flow kinetic (29), pulse radiolysis on peroxo-complexes in aqueous solution (30) and chemiluminescence data (31,32) .…”
Section: Fe(iv) and Singlet Oxygen In Fenton Reactionmentioning
confidence: 99%